Paradigma dan Esensi Manajemen Hubungan Masyarakat dalam Pendidikan Islam - Iffah Okta Afiana; Alfiana Ghani; Mardiyah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2023)
This article aims to examine a scientific theoretical model related to society, human thinking activities, leadership or management and the nature of society in the perspective of Islamic education. By using the research method library research (library research) this research was carried out by utilizing the literature from previous researchers. The analysis technique used is data or content analysis techniques. While the data collection instrument is carried out through reading activities in depth to reveal the essence of the various data collected. Data or content analysis is carried out to obtain valid inferences and can be re-examined in context. From the research it was found that public relations management can increase community empowerment. Through this empowerment, it makes the community have a community that has resilience in various sectors of life by making the public relations paradigm a reference in socializing. There needs to be a separate approach to prevent a misunderstanding between individuals and others. While the basic essence of public relations management is taken from the teachings or values ??of Quran and hadith.